2020
DOI: 10.1021/acsomega.0c01618
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy Progress via Lysosomal Depletion by Fluvastatin Nanoparticle Treatment in Breast Cancer Cells

Abstract: Fluvastatin (FLV) is a statin family member that may play a role in modulating a variety of medical disorders such as atherosclerosis and breast cancer. The present study addresses the ability of FLV to modulate the cellular immune response and provides a new nanosized FLV formula (self-nanoemulsifying delivery system, SNED) potentially more effective for suppression of breast cancer development. We monitored autophagic machinery through the expression of microtubule-associated protein 1A/1B-light chain 3 (LC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Fluvastatin belongs to the statin family and when used in vitro to treat breast cancer cells, it induced autophagy but with impaired lysosome function which may contribute to cell death. Moreover, a decrease of proinflammatory cytokines, such as IL-6 and TNF-a, was observed along with autophagy consequent effect in tumor immunity (230).…”
Section: Autophagy In Immune Cells: Dual Functions Shaping Tumor Respmentioning
confidence: 95%
“…Fluvastatin belongs to the statin family and when used in vitro to treat breast cancer cells, it induced autophagy but with impaired lysosome function which may contribute to cell death. Moreover, a decrease of proinflammatory cytokines, such as IL-6 and TNF-a, was observed along with autophagy consequent effect in tumor immunity (230).…”
Section: Autophagy In Immune Cells: Dual Functions Shaping Tumor Respmentioning
confidence: 95%
“…It should be noted that not only the endo-lysosomal system affects the nanoparticle but also vice versa. In recent studies, it was shown that cells treated with nanosized fluvastatin show increasing levels of autophagosome formation that competitively inhibit lysosomal activity [ 184 ]. It was shown that after internalization of nanoparticles functionalized with cell membrane penetrating peptide (TAT peptide), bystander nanoparticles, without any cell-penetrating ligands, can enter into the cells through the same endocytic pathway as functionalized nanoparticles [ 185 ].…”
Section: Self-assembled Amphiphilic Systems As Smart Drug Nanocarrmentioning
confidence: 99%
“…Pegylation of nanocarriers is documented to inhibit endosomal escape, which was testified in the transfection efficacy studies. Therefore, unique approaches were needed to answer this part of the PEG dilemma, including design of pH-responsive PEG-lipids or PEG-PEI conjugates, cleavable pegylated agents bridged by pH-sensitive bonds, e.g., ester, amide, disulfide, that undergo cleavage at low pH with the PEG residue released [ 184 , 193 , 194 ].…”
Section: Self-assembled Amphiphilic Systems As Smart Drug Nanocarrmentioning
confidence: 99%
“…Importantly, the recruiting of autophagy-related proteins family (Atg5-Atg12/ Atg16) is required for initiating autophagy, whereas the conversion of unlipidated Atg8, the microtubule-associated protein light chain-3B (LC3B), to lipidated LC3B is essential for the elongation and maturation step (16). Raising evidence indicated a direct association of autophagy in maintaining the solid tumors, in which the cells are in urgent need to resist harmful changes during cell division such as lacking nutrients and oxidative stress (hypoxia) (17,18). On the other hand, several studies reported the anticancer activity of the naturally purified glycoproteins such as the short peptides extracted from Achatina fulica mucus in treating breast cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%